Insights into Old English Lexicography: Lemmatisation of gĀn and Its Prefix-Formations using a Corpus-Based Database. (21st June 2021) - García Fernández, Laura
Abstract: This article contributes to Old English lexicography by providing a list of lemmas and inflectional forms for the Old English derived verbs (prefixed verbs) of gān 'to go'. Entries for these lemmas, if listed by Old English dictionaries, are often incomplete, but, more importantly, they are not based on a lemmatised corpus. This is particularly problematic in the case of languages like Old English that are rife with morphological variation. The methodology followed in this study comprises searches on a lexical database and manual revision of the hits. The searches are launched on the lemmatiser Norna, and the hits are checked with available lexicographical sources, secondary sources and annotated corpora. Finally, ambiguous cases are examined in their context. The final list of lemmas and inflectional forms amounts to 104 inflectional forms which are attributed to 14 different lemmas, including one lemma and up to 61 inflectional forms never before listed by dictionaries. Special attention is paid to the contrast between what is attested in the Old English corpora and what is available from the sources. In addition to providing insights into the inventory of lemmas and inflectional forms for the derivatives (prefixed verbs) of the verb gān as attested in The Dictionary of Old English Corpus, which was not available until now from lexicographical sources, this article contributes recommendations for the linguistic analysis of Old English using corpus-based lexical databases.